Identify The Relationship Between Scientific Writing Skills and Cognitive Skills During Laboratory Activities - Rahayu*, Dita Puji; Meiliyanti, Meiliyanti; Rabbani, Annas (Jurnal Pendidikan Sains Indonesia, 2024)
The lack of understanding about how scientific writing skills influence students' cognitive skills during laboratory activities. This study aimed to assess scientific writing skills and cognitive skills and explore their relationship among 49 first-semester science teacher candidates enrolled in a practical course on measurement tools and methods from February to June 2023. Cognitive skills were evaluated using reported response scores. Descriptive analysis revealed a spectrum of scientific writing skills, ranging from excellent to poor, among the participants, alongside generally low cognitive abilities. However, upon conducting correlation tests, it was found that there was no significant relationship between the ability to write reports and the response values (Sig = 0.117 0.05, rcount = 0.227 rtable = 0.281). The research findings suggest that scientific writing skills exhibit variance across different practical subjects, and notably, the ability to write reports does not appear to correlate with response scores. These insights shed light on the complex interplay between scientific writing proficiency and cognitive abilities during laboratory activities, urging further exploration into pedagogical strategies to enhance both skill sets in science education